Meaning and Function of Homework in Elementary School, its Effect on Student Achievement, Teachers’ Feedback Methods, and Parental Involvement - Erdal Küçüker; Erva Kaçar (Uluslararası Türk Eğitim Bilimleri Dergisi)
This research was conducted to examine the opinions of elementary school students, teachers, and parents about the meaning and function of homework, its effect on student achievement, teachers’ feedback methods, and parental involvement in homework. A phenomenological approach was employed in the study. Participants of the study consisted of 10 students at an elementary school in the Akçakale district of Şanlıurfa province, 10 teachers working at the same school during the 2021-2022 academic year, and 10 parents. Teachers, students, and parents participated in the study voluntarily. Data were collected through interviews. The interviews were recorded with the permission of the participants. After the audio recordings were transcribed, they were analyzed through content analysis. The findings of the analysis were presented in tables, and some of the participants' statements were quoted. Based on the findings, it was found that students had positive and negative feelings about homework, teachers, and parents built a positive relationship between homework and academic achievement, teachers' feedback methods were generally inadequate, and parents were sensitive about parental involvement in homework. Regarding these results, some suggestions for practice and research were developed.